TRIANGULAR MEMBERSHIP FUNCTIONS FOR SOLVING SINGLE AND MULTIOBJECTIVE FUZZY LINEAR PROGRAMMING PROBLEM. - Abbas, Iraq (Iraqi Journal of Science, 2024)
In this paper, fuzzy single and multiobjective linear programming models are presented. Both the objective function and the constraints are considered fuzzyly.The coefficient of the decision variable in the objective functions and the constraints, as well as the right-hand side of the constraints are assumed to be fuzzy numbers with triangular membership functions. The possibility programming approach is utilized to transform the fuzzy model into its crisp equivalent form, and then a suitable method will be used to solve the crisp problem.